Eosinophilic fasciitis associated with myositis: Report of four cases and review of the literature. (27th December 2018) - Liu, Yin; Zeng, Yanping; Xie, Yanchun; Gao, Likun; Chu, Hong; Xiao, Zheman; Lu, Zuneng
Abstract: Eosinophilic fasciitis is a rare scleroderma‐like syndrome with an unknown aetiology. The characteristics of this disorder include lymphoplasmacytic inflammation involving the subcutaneous fat septa and fascia. Eosinophilic myositis is diagnosed when inflammation extends into the muscles. Here, we describe four patients who developed eosinophilic fasciitis, three of whom developed eosinophilic fasciitis with myositis. Fascial and muscle biopsies were used to confirm the diagnoses. All the patients presented with musculoskeletal symptoms; their electromyographic examinations showed myogenic lesions [short‐duration, low‐amplitude and polyphasic motor unit action potentials (MUPs), so‐called myopathic changes, frequently with abnormal spontaneous activity], in contrast with findings from other reports.